Environmental Approach In Interior Design Education In Turkey - Derya Adıgüzel; Ayşen Ciravoğlu (Iconarp International Journal of Architecture and Planning, 2013)
These days there has been a severe encroachment on nature, a large amount of waste being generated, and natural resources being used irresponsibly during the design, application and usage phases of buildings. Environmental sensitivity is necessary during the construction of new buildings and re-usage of current buildings to resolve environmental problems. In order to increase environmental sensitivity, a great responsibility falls onto interior design along with other disciplines during the creation of living spaces. The accumulation of knowledge from career training and the level of awareness will determine the practical development of environmentally sensitive interior design. Therefore the purpose of this article is to make a determination of the current state of environmental design in interior design education in Turkey. The degree to which environmental design is reflected in the curricula of interior design departments was studied. The relationship between the awareness level of the students and the educational programs will be presented through three samples. Surveys were conducted at three universities that have varying degrees of environmental design within the interior design curricula. As a result, the importance of having an environmentally conscious design understanding within the curricula of interior design and recommendations for improving the environmental design awareness of students will be presented in this article.